2005
DOI: 10.1161/01.str.0000173159.65228.68
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Alcohol Consumption and Subclinical Carotid Atherosclerosis

Abstract: Background and Purpose-Epidemiologic studies have shown a J-shaped association between alcohol consumption and vascular diseases. However, only few studies have reported on the association between alcohol intake and subclinical atherosclerosis. The aim of the study was to investigate the relation between alcohol intake and carotid intima-media thickness (IMT) in participants of the population-based Study of Health in Pomerania. Methods-In 1230 men and 1190 women, the mean IMT of the right and left common carot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 36 publications
(30 reference statements)
6
36
2
Order By: Relevance
“…Data of the Atherosclerosis Risk in Communities (ARIC) study and the Three-City study found no relationship between alcohol consumption and IMT (Demirovic et al, 1993;Zureik et al, 2004). Data from the Study of Health in Pomerania showed an inverse correlation of alcohol consumption with IMT in men, whereas in women no correlation was seen (Schminke et al, 2005). In the Cardiovascular Health Study (CHS) of adults aged X65 years, only a moderate alcohol intake was inversely related to IMT, whereas a higher amount showed a positive correlation (Mukamal et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Data of the Atherosclerosis Risk in Communities (ARIC) study and the Three-City study found no relationship between alcohol consumption and IMT (Demirovic et al, 1993;Zureik et al, 2004). Data from the Study of Health in Pomerania showed an inverse correlation of alcohol consumption with IMT in men, whereas in women no correlation was seen (Schminke et al, 2005). In the Cardiovascular Health Study (CHS) of adults aged X65 years, only a moderate alcohol intake was inversely related to IMT, whereas a higher amount showed a positive correlation (Mukamal et al, 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Carotid intima-media thickness (IMT) is an established strong predictor of future coronary and cerebrovascular events and is presumed to reflect subclinical atherosclerosis; however, data in young or healthy individuals are limited and have yielded inconsistent results (Bots et al, 1997;Chambless et al, 1997;O'Leary et al, 1999;Lorenz et al, 2007). Some investigators found an inverse association in men but not in women, whereas others failed to show a relationship at all (Kauhanen et al, 1999;Zureik et al, 2004;Schminke et al, 2005;Lee et al, 2009). Previous studies have mainly been performed in middle-aged or elderly subjects with established risk factors for CVD.…”
Section: Introductionmentioning
confidence: 99%
“…Authors found thinner IMT than those in highrisk populations, suggesting that an increased IMT might reflect local atherosclerosis [38] . Protective factors such as HDL cholesterol or regular and moderate alcohol consumption are probably important determinants of the early stages of atherosclerosis in these low-risk populations [39] .…”
Section: Is Imt a Predictor Of Future Vascular Events In Coronary Or mentioning
confidence: 99%
“…128 A U-or J-shaped relationship was observed between the level of alcohol intake and severity of carotid atherosclerosis in the Bruneck Study and the Study of Health in Pomerania. 129,130 Although the results of epidemiological studies have been inconsistent, light-to-moderate consumption seems to inhibit the development of carotid atherosclerosis.…”
Section: Cerebrovascular Diseasementioning
confidence: 99%